Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


f(x)= \frac{x-5}{2x+3}
y(2x+3) = x-5
2xy+3y = x-5
x(2y-1) = -5-3y
x = \frac{-5-3y}{2y-1}

Switching x and y, the final answer is:
y= \frac{-5-3x}{2x-1}
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts